Effect of tempe waste on excreation of purine derivatives and microbialâN supply in lactating Etawah crossbred goats - Astuti, D.A; Wina, E (Indonesian Animal Sciences Society, 2002)
The aim of this study was to evaluate excretion of purine derivatives and microbialâN supply in lactating Etawah crossbred goats fed with fermented soybean waste. Sixteen first lactating goats were randomly allotted into four dietary treatment groups that received 50% king grass plus R1: 50% concentrate, R2: 25% concentrate and 25% fresh tempe waste, R3: 25% concentrate and 25% fermented tempe waste, and R4: 25% concentrate and 25% gelatinizing of liquid tempe waste. Fermented tempe waste was made by fermentation of tempe waste (seed content of soybean) using Aspergillus niger, while for the gellatinizing of liquid tempe waste was made by gelatinized with maize flour. Protein balance studies were conducted during two week trial and at the end of the research. Urinary protein and purine derivatives were collected for analysis. MicrobialâN supply was calculated from purine derivatives excretion. Results showed that nitrogen consumptions were significantly different between R4 and three other treatments and apparent digestible nitrogen in R3 were higher than that of R4 (P<0.05). The nitrogen retention in R1 and R3 were higher than that of R2 and R4. Urinary purine derivatives in this study showed that allantoin, xanthine and hypoxanthine in R3 were higher than that of R4, while R1 and R2 were the same and the highest uric acid excretion and total purine derivatives were observed in R3. MicrobialâN supply were significantly different between all treatments where R3 was the highest. This research concluded that fermented soybean waste had the highest total purine derivatives excretion and microbialâN supply to the lactating Etawah crossbred goats. Â Key words: Etawah crossbred goats, Aspergillus niger, allantoin, xanthin and hypoxanthin